2007
DOI: 10.1016/j.febslet.2007.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein folding and the role of EDEM1, EDEM2 and EDEM3 in degradation of folding‐defective glycoproteins

Abstract: Proteins synthesized in the endoplasmic reticulum (ER) lumen are exposed to several dedicated chaperones and folding factors that ensure efficient maturation. Nevertheless, protein folding remains error-prone and mutations in the polypeptide sequence may significantly reduce folding-efficiency. Folding-incompetent proteins carrying N-glycans are extracted from futile folding cycles in the calnexin chaperone system upon intervention of EDEM1, EDEM2 and EDEM3, three ER-stressinduced members of the glycosyl hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 63 publications
(112 reference statements)
1
100
0
Order By: Relevance
“…The participation of posttranslational modification in protein degradation is not unusual with the most common being the targeting of proteins for proteolytic destruction by ubiquitinylation. The specialized processing of N-linked glycans on misfolded proteins in the endoplasmic reticulum also triggers a pathway of proteolytic destruction (26,27). The role of the posttranslational modifications in these cases, however, is thought to occur upstream of proteolysis, rather than by the direct recognition of the modification by a protease active site.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of posttranslational modification in protein degradation is not unusual with the most common being the targeting of proteins for proteolytic destruction by ubiquitinylation. The specialized processing of N-linked glycans on misfolded proteins in the endoplasmic reticulum also triggers a pathway of proteolytic destruction (26,27). The role of the posttranslational modifications in these cases, however, is thought to occur upstream of proteolysis, rather than by the direct recognition of the modification by a protease active site.…”
Section: Discussionmentioning
confidence: 99%
“…There is at least some distinction from the most upstream components of the glycoprotein pathway, as many of these proteins interact with the chaperone BiP instead of calnexin or calreticulin (15,16), and at least some of these nonglycosylated ERAD substrates require the ERAD machinery-associated protein Herp (17). We recently found that, surprisingly, EDEM1, a central player in glycoprotein ERAD (10,18,19), can bind a glycoprotein ERAD substrate in a glycan-independent manner and that its overexpression or up-regulation during the unfolded protein response overrides the mannose trimming requirement for ERAD. This hinted to a potential role in nonglycosylated protein ERAD.…”
Section: Research On Ermentioning
confidence: 99%
“…4A, lane 4). Human EDEM proteins share an overall ϳ90% amino acid sequence identity with their murine orthologues (26). To confirm the lack of inhibitory activity of these EDEM proteins, human EDEM proteins were ectopically expressed with HIV-1 in 293T cells, and the Env expression was determined.…”
Section: Identification Of Ermani From the Erad Pathway That Inhibitsmentioning
confidence: 99%